Implementing Joyful Learning Strategy Using Wordwall in Order to Improve Reading Comprehension Skills - Aryani Purnaning Rahmawati; Putu Ranti Wijayanti (UM Purwokerto Press, 2022)
Wordwall become one of ICT development which ease students to develop reading skills. This game applies new words and unfamiliar words to the students. The design of this application is simplicity to use by the teachers and the students. There are several characteristic of the application, namely: cumulative collections of words, it can be designed for specific instructional purposes, interactive, printable and providing scaffolds conversation in order to create students’ critical thinking. On the other hand, this application requires more time to made by the teachers even it has charge. Furthermore the students will feel enjoy using this application during online learning.